1997
DOI: 10.1002/(sici)1096-9861(19970811)384:4<517::aid-cne3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the nucleus of the basal optic root in pigeons (Columba livia) revealed with biotinylated dextran amine

Abstract: The nucleus of the basal optic root (nBOR) of the accessory optic system is known to be involved in the analysis of the visual consequences of self-motion. Previous studies have shown that the nBOR in pigeons projects bilaterally to the vestibulocerebellum, the inferior olive, the interstitial nucleus of Cajal, and the oculomotor complex and projects unilaterally to the ipsilateral pretectal nucleus lentiformis mesencephali and the contralateral nBOR. By using the anterograde tracer biotinylated dextran amine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 67 publications
7
93
0
1
Order By: Relevance
“…The dorsal thalamic nucleus receives vestibular [19] and optic flow cues [21,22] that are used for path integration and flight stabilization. Therefore, the activation of this region during displacement from the home loft, as well as the homeward flight, is not surprising ( figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The dorsal thalamic nucleus receives vestibular [19] and optic flow cues [21,22] that are used for path integration and flight stabilization. Therefore, the activation of this region during displacement from the home loft, as well as the homeward flight, is not surprising ( figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding a possible direct connection from the AOS to the cerebellar cortex, this has been described in several nonmammals (fish: Finger and Karten, 1978;turtle: Reiner and Karten, 1978;Weber et al, 2003;pigeon: Brauth and Karten, 1977;Wylie and Linkenhoker, 1996;Wylie et al 1997; but see Montgomery et al, 1981, frog), but its presence in mammals is controversial. Thus, whereas a direct AOS-cerebellar connection was described in chinchilla (Winfield et al, 1978) and tree shrew (Haines and Sowa, 1985), none was found in rat, rabbit, cat and marmoset monkey (Kawasaki and Sato, 1980;Feran and Grasse, 1982;Giolli et al, 1984Giolli et al, , 1985aGiolli et al, , 1988bBlanks et al, 1995).…”
Section: Precerebellar Projections Of the Aosmentioning
confidence: 99%
“…12,19,20 Nuclei of the accessory optic system project to areas of the inferior olive (IO) that provide climbing fiber input to the contralateral vestibulocerebellum (VbC). 1,[6][7][8]20,33 In pigeons, the VbC consists of folium X (nodulus), the ventral lamella of folium IXc,d (ventral uvula) and the auricle (flocculus), which is the lateral extension of these folia. 18 Previous electrophysiological studies of the pigeon VbC have shown that complex-spike (CS) activity of Purkinje cells (which reflects climbing fiber activity) responds best to specific patterns of optic flow resulting from either self-translation or self-rotation.…”
mentioning
confidence: 99%